2018
DOI: 10.1002/1873-3468.13088
|View full text |Cite
|
Sign up to set email alerts
|

Computational modeling highlights the role of the disordered Formin Homology 1 domain in profilin‐actin transfer

Abstract: Formins accelerate actin polymerization, assumed to occur through flexible FH1 domain mediated transfer of profilin-actin to the barbed end. To study FH1 properties and address sequence effects including varying length/distribution of profilin-binding proline-rich motifs, we performed all-atom simulations of mouse mDia1, mDia2; budding yeast Bni1, Bnr1; fission yeast Cdc12, For3, and Fus1 FH1s. We find FH1 has flexible regions between high propensity polyproline helix regions. A coarse-grained model retaining … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
29
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 62 publications
(128 reference statements)
3
29
0
Order By: Relevance
“…Our experiments with double-tract variants of Bni1p indicated that neighboring polyproline tracts do not compete to bind profilin-actin ( Figure 6D). This is consistent with published crystallographic and molecular modeling studies, which demonstrated that FH1 domains can accommodate simultaneous binding of multiple profilin-actin complexes to neighboring tracts (18,19). Instead, competition arises when multiple tracts compete to deliver profilin-actin to the barbed end ( Figure 6E).…”
Section: Competition For Delivery Of Multiple Polyprolinebound Profilsupporting
confidence: 90%
See 3 more Smart Citations
“…Our experiments with double-tract variants of Bni1p indicated that neighboring polyproline tracts do not compete to bind profilin-actin ( Figure 6D). This is consistent with published crystallographic and molecular modeling studies, which demonstrated that FH1 domains can accommodate simultaneous binding of multiple profilin-actin complexes to neighboring tracts (18,19). Instead, competition arises when multiple tracts compete to deliver profilin-actin to the barbed end ( Figure 6E).…”
Section: Competition For Delivery Of Multiple Polyprolinebound Profilsupporting
confidence: 90%
“…What determines the number of polyproline tracts encoded by a formin's FH1 domain? This number ranges among formin isoforms from as few as 1 to as many as 14 (18). Because the probability of simultaneous binding of multiple profilin-actin complexes increases with the number of polyproline tracts, competition for delivery should strongly attenuate the elongation rates mediated by formins with large numbers of tracts.…”
Section: A Role For Gating In Regulating the Competition Among Polyprmentioning
confidence: 99%
See 2 more Smart Citations
“…It has recently been reported that different surface-anchoring schemes, putting different constraints on formin rotation may affect its ability to elongate filaments (Yu et al, 2017) . Here, for FH1-side anchored formins, the FH1 domain can be considered as a flexible linker with a contour length of~40 nm, connecting the formin to the surface (Horan et al, 2018) . In contrast, when formins are anchored by their FH2 side, the DAD domain, which lies downstream of FH2 and is composed of a short alpha-helix followed by an unstructured region, can be considered as a linker of~10 nm in contour length (Kühn and Geyer, 2014) .…”
Section: Resultsmentioning
confidence: 99%